Detection of abnormally shaped ears by a trained non-specialist allows for early non-surgical intervention. (July 2018) - Lu, Daphne Y.D.; Pauwels, Julie; Jin, Lisa; Kozak, Frederick K.; Chadha, Neil K.
Abstract: Introduction: Many children are born with abnormally-shaped ears, including protruding ears or unusually-shaped outer ears. While the majority are benign, these may cause significant issues with self-esteem and bullying in childhood. Early molding can resolve some of these abnormalities, avoiding the need for future corrective surgery. However, newborns with these abnormalities are rarely identified early, within the first few days of life, when molding is most effective. In this study, we investigate whether a trained non-specialist can correctly identify ear shape abnormalities in newborns. Methods: A non-specialist (medical student) was trained on normal and abnormal ear anatomy using photographs and descriptions. Newborns <72 h of age were recruited from maternity wards. Newborns' ears were photographed and these images were assessed independently by two specialists and the non-specialist. External ear shape was classified as either normal or abnormal based on pre-determined criteria. Results: A total of 661 ears of 334 newborns were photographed and assessed. High inter-rater agreement was achieved with a kappa statistic of 0.863 (SE 0.078). The non-specialist detected abnormally-shaped ears with a sensitivity and specificity of 90.9% and 91.1% respectively. Conclusions: Our study illustrates that non-specialist can be trained to accurately detect newborn ear abnormalities, providing a cost-effective means of ensuring that these children's health care needs are met in a timely fashion. Specifically, we recommend the integration of ear shape assessment into currently established programs such as the newborn hearing screening program.